KULTIVASI MIKROALGA Spirulina platensis DALAM MEDIA POME DENGAN VARIASI KONSENTRASI POME DAN KOMPOSISI JUMLAH NUTRIEN - Fitria Yuli Anggita Sari; I Made Aditya Suryajaya; H Hadiyanto (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Indonesia and Malaysia are known as the largest countries of palm oil producer in the world. Along the development of palm oil industry in Indonesia, there is more liquid waste from manufacturing process of palm oil which is known as Palm Oil Mill Effluent (POME). POME has been treated using method of aerobic and anaerobic ponds to reduce COD and BOD contents , whereas POME still contains nutrients such as C,N,P which are useful as a nutrient for the growth of microalgae. In this research,cultivation of Spirulina platensis cultivated in POME media with various concentrations of 20%, 40%, and 60% V . Urea, NaHCO3, and TSP were given each two days as a nutrient. The cultivation process carried out for 7 days with aeration and 24 hours lighting.The result shows that the best cultivation media is POME with a concentration of 20%. The best nutrient composition is the addition of 25 mg/l Urea, TSP 50 mg/l and 200 mg/l NaHCO3. At the same treatment on a variety of media is obtained that the maximum growth rate of Spirulina platensis is μ = 0.128/day. The nutrient savings gained from the use of POME as a cultivation media is: Carbon by 42,23 % - 129,71 % and 41,46% - 124.44%. for Nitrogen. This research also showed that C,N,P contents of POME decrease by 20,60% - 84,69% ; 87,52% - 93,47% and 29,44% - 76,66% respectively.